The Definitive Guide to Jython: Python for the Java™ Platform - Juneau, Josh (Apress, 2013)
This book is organized so that each chapter is encapsulated as its own entity and can be read separately from the others. This provides the ability to jump around the book if you’d like, or read it from start to finish. Some chapters contain references to other parts of the book and this book builds upon itself to guide a novice or a seasoned developer into becoming an expert Jython programmer. Since this is a multi-author book, each of the chapters was written by an individual author or a pair of authors, and because of this you may find that the chapters each contain a unique touch, but they are orchestrated in such a way that they work very well together.